Nutrición y calidad - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
In 1984 the nutrition and quality lab. evaluated 390 advanced lines from the EP 84 for seed quality, percentage of water absorbance from dry wt., presence of hard and broken seeds, av. cooking time, soup quality, and protein content. Results suggest that shiny grains tend to resist absorbing water during soaking and the opaque colors present less seed hardness. The influence of location, harvest time, and var. on cooking time, seed hardness, and CP content was also studied to determine if genetic or environmental variability, or interaction of the 2, can influence some cooking and nutritive seed characteristics. Cooking time and hardness of wild lines of the common bean and resistance to storage insects were assessed by measuring the cooking time in 9 resistant and 5 susceptible lines and the percentage hardness in 18 resistant and 5 susceptible lines. There were no significant differences among the lines for either variable. (CIAT)